THE EVOLUTION OF MANAGEMENT APPROACHES IN THE 21ST CENTURY – ADAPTIVE MODELS OF TRANSFORMATION OF ORGANIZATIONAL STRUCTURES (Marketing Journal, 2025)
This paper explores the evolving landscape of management practices in contemporary organizations, with a particular focus on the rise of Agile and adaptive methodologies. Initially developed within the IT sector, Agile principles have gained widespread rel evance as a strategic response to the volatility and uncertainty of today’s business environment. The study highlights the core factors driving Agile adoption, outlines key implementation frameworks such as Scrum, Kanban, and OKR, and examines their impact on organizational structure and culture. The findings suggest that adaptability is no longer a tactical advantage but a foundational element of modern management philosophy essential for sustaining long -term competitiveness.
Keywords: Agile; adaptive management; Scrum; Kanban; OKR; organizational transformation; team autonomy; customer -centricity; VUCA environment